The Water Man [videorecording (DVD)] - Oyelowo, David; Dawson, Rosario; Chavis, Lonnie; Miller, Amiah, 2004-; Molina, Alfred, 1953-; Bello, Maria, 1967- (RLJ Entertainment, Inc., 2021)
Gunner's mother is very ill, but he believes a local legend about "the Water Man" who knows how to live forever, so he and a mysterious girl named Jo set off into the Wild Horse forest in order to hunt down the legend. The deeper they go into the woods, it becomes more strange and more dangerous, but Gunner's father is coming after them and will stop at nothing to rescue his son.